Hitler’s political action as anticipated by Churchill - Pereira, Américo (2021)
Having read Hitler’s Mein Kampf, Churchill understood what he calls "the granite pillars" of the Nazi Leader’s policy, thus knowing, step by step, what the Dictator wanted to do, was going to do. This allowed Churchill to start counter acting successfully Hitler’s actions even before being the Prime Minister of Great Britain. Thus Mein Kampf became both Hitler’s and Churchill’s guide, leading them in quite opposite directions.